25(OH)D Status in Metabolic Syndrome, Metabolic Syndrome Components, and Healthy Adult - Efriwati Efriwati; Fitrah Ernawati; Nunung Nurjanah; Elisa Diana Julianti; Galih Kusuma Aji; Dian Sundari; Fifi Retiaty; Aya Yuriestia Arifin (Amerta Nutrition)
Background: Vitamin D supplementation to prevent Metabolic Syndrome (MetS) has been widely implemented in developed countries and is now being introduced in developing countries. However, recent studies have shown no association between vitamin D and MetS in adults.